Facial Bone Reconstruction Using both Marine or Non-Marine Bone Substitutes: Evaluation of Current Outcomes in a Systematic Literature Review - Cicciù, Marco (Mar Drugs, 2018)
The aim of the present investigation was to systematically analyse the literature on the facial bone reconstruction defect using marine collagen or not and to evaluate a predictable treatment for their clinical management. The revision has been performed by searched MEDLINE and EMBASE databases from 2007 to 2017. Clinical trials and animal in vitro studies that had reported the application of bone substitutes or not for bone reconstruction defect and using marine collagen or other bone substitute material were recorded following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The first selection involved 1201 citations. After screening and evaluation of suitability, 39 articles were added at the revision process. Numerous discrepancies among the papers about bone defects morphology, surgical protocols, and selection of biomaterials were found. All selected manuscripts considered the final clinical success after the facial bone reconstruction applying bone substitutes. However, the scientific evidence regarding the vantage of the appliance of a biomaterial versus autologous bone still remains debated. Marine collagen seems to favor the dimensional stability of the graft and it could be an excellent carrier for growth factors.